Learn java for android development - Friesen, Jeff (Apress, 2014)
Learn Java for Android Development, Third Edition, is an update of a strong selling book that now includes a primer on Android app development (in Chapter 1 and Appendix C, which is distributed in the book's code archive). This book teaches programmers the essential Java language skills necessary for effectively picking up and using the new Android SDK platform to build mobile, embedded, and even PC apps, especially game apps. Android development is hot, and many programmers are interested in joining the fun. However, because this technology is based on Java, you should first obtain a solid grasp of the Java language and its APIs in order to improve your chances of succeeding as an effective Android app developer. This book helps you do that. Each of the book's 16 chapters provides an exercise section that gives you the opportunity to reinforce your understanding of the chapter's material. Answers to the book's more than 700 exercises are provided in an appendix. A second appendix provides a significant game-oriented Java application, which you can convert into an Android app. Once you complete this one-of-a-kind book written by Jeff Friesen, an expert Java developer and JavaWorld.com columnist, you should be ready to begin your indie or professional Android app development journey.